Examining the coupling relationship between industrial upgrading and eco-environmental system in resource-based cities in China - Lei, Yu; Chen, Yongxiang; Zhang, Lanyue; Lu, Yifu (Frontiers in Public Health, 2025)
IntroductionThe long-term extensive development of resource-based cities makes them face problems such as resource exhaustion, industrial structure imbalance, ecological environment deterioration, which urgently need to carry out green transformation.MethodsIn this study, Entropy-CRITIC-TOPSIS model and coupling coordination degree model were constructed to estimate and analyze the coordinated development level of industrial structure upgrading and ecological environment of 19 resource-based cities in Northeast China from 2010 to 2021.ResultsThe results showed that the coupling coordination situation between industrial structure rationalization and ecological environment in 19 resource-based cities were unsatisfactory, and the proportion of uncoordinated development between industrial structure rationalization and ecological environment was as high as 89.47%. In comparison, the coupling coordination situation between industrial structure advancement and ecological environment were relatively better, with all cities’ industrial structure upgrading and ecological environment systems being basically coordinated or above.DiscussionThis suggests that resource-based cities in Northeast China should still focus on improving the rational allocation of resources, environmental protection, and coordinated development of resource utilization. The conclusion of this study provides a theoretical basis for the sustainable development of domestic resource-based cities, and can also be used as a reference for domestic and foreign resource-based cities or regions.